Pengaruh Brand Image, Brand Awareness Dan Brand Trust Terhadap Keputusan Pembelian Smartphone Merek Apple - Dita Zulia Pramesti; I Nyoman Sujana (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
The research was conducted with the aim of knowing the influence of brand image, brand awareness and brand trust on purchasing decisions of apple brand smartphones. This research includes the type of causal research. The population in this study were 40 students of the Economic Education Study Program at Ganesha University of Education who had or are currently using Apple brand smartphones. The sample of this research is 40 students. Saturated sample or total sampling is used in the sampling technique. Methods of data collection in the form of questionnaires and in-depth interviews. Data processing method using multiple linear regression. The hypothesis test used included t test and F test. The results showed that brand image had a partially positive and significant effect on purchasing decisions, then brand awareness had a positive and partially significant effect on purchasing decisions, and brand trust had a partially positive and significant effect on buying decision. The test results together show that brand image, brand awareness and brand trust have a positive and significant simultaneous effect on purchasing decisions for Apple brand smartphones.